2006
DOI: 10.1089/fpd.2006.3.190
|View full text |Cite
|
Sign up to set email alerts
|

Listeriosis Associated with Gorgonzola (Italian Blue-Veined Cheese)

Abstract: We describe a case of listeriosis in Italy associated with the consumption of cheese. Opened samples of two brands of gorgonzola (Italian blue-veined cheese; referred to as brands "B" and "C") were collected from the patient's refrigerator. Unopened samples of the brand suspected to be the source of infection (brand B) were taken from the store where the cheese had been purchased, other local stores, and the production plant. Listeria monocytogenes serotype 1/2b was isolated from the patient and from the opene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…In 2003, a case of listeriosis associated with the consumption of Gorgonzola, was described. Pulsed-Field Gel Electrophoresis (PFGE) and Random Amplification of Polymorphic DNA (RAPD) subtyping showed that the clinical isolate was indistinguishable from those collected from the processing plant and that closely related isolates persisted for five months in the dairy (Gianfranceschi et al, 2006). Different subtyping methods proved that specific isolates of L. monocytogenes are able to establish persistent contaminations in dairy premises for months and sometimes even years (Chambel et al, 2007;Leite et al, 2006;Rückerl et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In 2003, a case of listeriosis associated with the consumption of Gorgonzola, was described. Pulsed-Field Gel Electrophoresis (PFGE) and Random Amplification of Polymorphic DNA (RAPD) subtyping showed that the clinical isolate was indistinguishable from those collected from the processing plant and that closely related isolates persisted for five months in the dairy (Gianfranceschi et al, 2006). Different subtyping methods proved that specific isolates of L. monocytogenes are able to establish persistent contaminations in dairy premises for months and sometimes even years (Chambel et al, 2007;Leite et al, 2006;Rückerl et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The combination of standard cheese manufacture protocols with HP treatment could produce a high quality cheese without health risks due to pathogen contamination, such as Salmonella enteritis or L. monocytogenes (Gianfranceschi et al, 2006;Keene, 1999;Ratnam, 1999), as pathogens, as well as undesirable bacteria are inactivated by pressure, yet, without the negative effect on cheese flavour occurring after pasteurisation (Grappin & Beuvier, 1997). HP treatment of raw milk spiked with L. monocytogenes resulted in Camembert cheese with undetectable levels of the pathogen after 3 weeks of ripening (Linton et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…; Gianfranceschi et al . ). Soft cheese, especially, provides excellent growth conditions, and is often involved in the outbreaks of listeriosis (Melanie and Siegfried ).…”
Section: Introductionmentioning
confidence: 99%